High-Methoxyl Apple Pectin Improves Rheological Properties and Storage Stability of the Flavored Probiotic Yogurt Drinks, Compared to Pomegranate Pectin - Bahareh Sarmadi; Parang Nikmaram; Amir-Mohammad Mortazavian-Farsani; Hossein Kiani; Mohammad Mousavi; Elham Khanniri; Reza Mohammadi; Adriano G da Cruz (Applied Food Biotechnology, 2022)
Background and Objective: Use of pectin has attracted interests in food and nutraceutical industries, owing to its positive effects on stability of dairy drinks and potential health benefits to humans. Furthermore, demands for the production of stable fermented milk drinks during storage period is high. Therefore, the aim of this study was to assess effects of apple and pomegranate pectins as stabilizers on various characteristics of probiotic yogurt drinks.